Hearing Allah's Call : Preaching and Performance in Indonesian Islam - Millie, Julian, 1967- (Book collections on Project MUSE., 2017)
Hearing Allah's Call changes the way we think about Islamic communication. In the city of Bandung in Indonesia, sermons are not reserved for mosques and sites for Friday prayers. Muslim speakers are in demand for all kinds of events, from rites of passage to motivational speeches for companies and other organizations. Julian Millie spent fourteen months sitting among listeners at such events, and he provides detailed contextual description of the everyday realities of Muslim listening as well as preaching. In describing the venues, the audience, and preachers--many of whom are women--he reveals tensions between entertainment and traditional expressions of faith and moral rectitude. The sermonizers use in-jokes, double entendres, and mimicry in their expositions, playing on their audiences' emotions, triggering reactions from critics who accuse them of neglecting listeners' intellects. Millie focused specifically on the listening routines that enliven everyday life for Muslims in all social spaces--imagine the hardworking preachers who make Sunday worship enjoyable for rural as well as urban Americans--and who captivate audiences with skills that attract criticism from more formal interpreters of Islam. The ethnography is rich and full of insightful observations and details. Hearing Allah's Call will appeal to students of the practice of anthropology as well as all those intrigued by contemporary Islam.